ECMO survivors' quality of life and needs after discharge: A descriptive, comparative cross-sectional pilot study. (August 2020) - Tiedebohl, Jennifer M.; DeFabio, Michelle E.; Bell, Theodore; Buchko, Barbara L.; Woods, Anne B.
Abstract: Objectives: To describe gender differences in health-related quality of life and characterise discharged patients' perceptions of follow-up needs after extracorporeal membrane oxygenation. Research methodology/design: A descriptive, comparative cross-sectional pilot design was used. Adult patients receiving extracorporeal membrane oxygenation discharged between January 1, 2016 and March 31, 2018 participated in telephone interviews. Setting: A 580-bed community teaching hospital in south central Pennsylvania. Main outcome measures: Health-related quality of life was measured with the Rand 36-item Short Form Health Survey. Open-ended questions identified post-discharge healthcare services and perceived follow-up needs. Results: Of 30 eligible patients, 24 completed a telephone interview. All health-related quality of life dimensions, except for role-emotional and mental health, were lower in post- extracorporeal membrane oxygenation patients at follow-up compared to national norms. Women scored lower than men in all health-related quality of life dimensions. The most frequent post-discharge services used were physical therapy (66.7%), rehabilitation (62.5%) and occupational therapy (54.2%). The need for coordination of care post-discharge was identified. Conclusions: Given long-term sequelae of extracorporeal membrane oxygenation on health-related quality of life and gender differences in health-related quality of life outcomes, ongoing interdisciplinary follow-up is imperative to ensure comprehensive patient management across the continuum of care.